On the solvability of a semiperiodic boundary value problem for a pseudohyperbolic equation - Orumbayeva, N.T.; Tokmagambetova, T.D. (Filomat, 2023)
The solvability of the boundary value problem for pseudohyperbolic equations of the third order is investigated. For the problem under study, an algorithm for finding an approximate solution is proposed and sufficient conditions for unique solvability are established